SEMIOTIC HIDDEN CODES IN THE SHORT STORY “A ROSE FOR EMILY” BY WILLIAM FAULKNER - Satria, ROBBY (LPPM Universitas Muhammadiyah Sumatera Barat, 2018)
This research discusses the application of Semiotic theory proposed by RollandBarthes which describes that literary work has some symbolic codes viewed from Semioticstudies. In this analysis the writer discusses a short story “A Rose for Emily by WilliamFaulkner published in 1930. Here, the writer wants to prove the existence of some symboliccodessemiotically in the short story.This research is qualitative research by using descriptive method. Data is gained bylibrary research method and other sources taken from the web. In this research, the data isanalysed based on its relationship with the purpose of the research both instrinsic and extrinsicelement in literary work, then applying five codes in Semiotic theory proposed by Barthes.After applying the symbolic codes into the short story, the writer found there are threesymbolic codes hidden in “A Rose for Emily”, proairetic, hermeneutic, and cultural code. Theproairetic code gives the reader explanation about what happen to the main character duringher life and the cause of her madness. The hermeneutic code gives the reader the explanationabout the madness of the main character. Finally the cultural code in “A Rose for Emily” isregarding from family status too high will cause the bad effect to the member of the family.The writer also finds the similarity within the cultural code about the culture of the white toindifference the African American people.